Correction: Polymers as advanced antibacterial and antibiofilm agents for direct and combination therapies. Issue 16 (5th April 2023) - Si, Zhangyong; Zhong, Wenbin; Prananty, Dicky; Li, Jianghua; Koh, Chong Hui; Kang, En-Tang; Pethe, Kevin; Chan-Park, Mary B.
Abstract : Correction for 'Polymers as advanced antibacterial and antibiofilm agents for direct and combination therapies' by Zhangyong Si et al., Chem. Sci., 2022, 13, 345–364, ; https://doi.org/10.1039/D1SC05835E .